COST ANALYSIS OF JAMKESMAS INPATIENT TREATMENT IN PANEMBAHAN SENOPATI HOSPITAL, BANTUL IN 2008 - Rahma Artemisia; Ali Gufron Mukti; Tri Murti Andayani (Faculty of Pharmacy, Universitas Gadjah Mada)
Jamkesmas is social assistance health services program to poor society. This program is aimed to make cross subsidy health services for all poor society. This research is aimed at identifying the characteristics of patients, verification of Jamkesmas, average discrepancy of therapy cost, and average discrepancy of medicine cost. This research uses non‐experimental descriptive design, which is using proportional random sampling method that collected retrospectively. The result shows that appendicitis patient that need inclution criteria is 37 cases, of acutegastroenteritis (GEA) is 33 cases, of hypertension is 31 cases, of urinary tract infections is 32 cases , and of acute respiratory infection is 38 cases. The total amount of claims of Jamkesmas inpatient in 2008 is Rp 6.152.995.376, of the payable claims is Rp 6.053.265.909, and of the non‐payable claims is Rp 119.729.467. The average discrepancy cost of Jamkesmas verification and direct medical cost on receipt of appendicitis therapy is 56.028 ± 299.686, of acutegastroenteritis (GEA) is Rp ‐ 12.266 ± 204.275,, of hypertension is Rp 118.697 ± 329.572, of urinary tract infections is Rp 155.582 ± 696.428, and of acute respiratory infection is Rp 86.417 ± 156.541. The average discrepancy of medicine cost of Jamkesmas verification and medicine cost on receipt of appendicitis therapy is Rp ‐424.818 ± 444.459, of acutegastroenteritis (GEA) is Rp ‐ 31.110 ± 96.157, of hypertension is Rp ‐67.001 ± 114.541, of urinary tract infections is Rp 41.635 ± 353.945, and of acute respiratory infection is Rp 32.955 ± 132.815. Key words : Cost Analysis, Inpatient, Jamkesmas, RSUD Panembahan Senopati Bantul